Hambatan Kerja Sama Energi APG dari Perspektif Realisme Politik - Muhammad Naufal Musri; Silvia Dian Anggraeni (Andalas Institute of International Studies, 2021)
The current development of the world economy has driven the Southeast Asia region as one of the regions with the fastest economic growth. This is supported by a large population and high total economic value. These characteristics make countries in the Southeast Asia region have a great deal in the economic sector and thus impacted on massive energy use. To be able to meet these energy needs, the integrated ASEAN Power Grid energy cooperation networks is one of the steps taken by the ASEAN. Initiated in 1997 under the framework of ASEAN Vision 2020, the regional cooperation has not yet reached its expected outcomes. Through the approach of political realism based on status quo behavior which considers energy as a strategic commodity, this research analyses the impediments of the development of electrical energy infrastructure cooperation. The research focuses on the qualitative methods used in examining the political behavior of ASEAN states through secondary data collection and textual analysis. The result shows that the cycle of political realism has hindered the progress of the APG development in each of its member countries.